Relationship Between Knowledge Attitudes and Actions of Mother Who Have Babies 6-12 Months With Exclusive Breast Feeding in Tatan High Village Binjai Timur Sub-District in 2023 - Vivi Santri, Yuni; Lumbantobing, Pratiwi; Beru Perangin-angin, Susi Amenta (International Archives of Medical Sciences and Public Health, 2023)
Giving exclusive breastfeeding to babies also means giving big gifts in the form of the best immunization, complete nutrition, healthy drinks and life water to babies. In the process of exclusive breastfeeding, there are many disturbances which in principle are rooted in a lack of knowledge, self-confidence, family support and the surrounding environment. The low knowledge of mothers about the benefits of breastfeeding and lactation management from pregnancy to delivery will have a good impact on the mother's attitude which can influence behavior towards exclusive breastfeeding. Based on the results of the initial survey conducted by the researchers, it was shown that of the 7 mothers interviewed, there were 5 mothers who did not breastfeed their babies 6-12 months. This study aims to determine the relationship between knowledge, attitudes and actions of mothers who have babies 6-12 months by giving exclusive breastfeeding in the Highland Village, East Binjai District in 2023. This research is an analytic study with a cross-sectional study design. The population in this study were all mothers who had babies over 6-12 months in the Highland Village, East Binjai District, totaling 37 people. The research sample is used as the total sampling. Research data processing consists of editing, coding, entry, cleaning, tabulating. Data analysis consisted of univariate and bivariate with the Chi Square test. The results showed that there was a relationship between mother's knowledge and exclusive breastfeeding (p = 0.002). There is a relationship between mother's actions and exclusive breastfeeding (p = 0.001). Therefore, it is important for mothers of babies to take the time to participate in counseling held by health workers at the Puskesmas about the benefits of exclusive breastfeeding for babies so that they can increase the knowledge and attitudes of baby mothers in giving exclusive breastfeeding to babies.